Workload Burnout Distress and Turnover Intention Path Analysis: Analisis Jalur Beban Kerja, Kelelahan, Stres, dan Niat Pindah Pekerjaan - Vera Firdaus; Nilamsari Zahrina Avvrilia (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Employee retention remains a critical issue in human resource management due to persistent turnover intention in labor-intensive industries. Specific Background Employees at PT. XYZ Pasuruan experience workload pressure and burnout symptoms that may generate psychological distress and intentions to leave the organization. Knowledge Gap Previous studies commonly tested workload and burnout directly on turnover intention without positioning distress as an intervening mechanism. Aims This study analyzes the relationships among workload, burnout, distress, and turnover intention and tests the mediating role of distress. Results Using a quantitative design with purposive sampling of 100 production employees and Structural Equation Modeling, workload shows a positive and significant relationship with turnover intention, burnout significantly relates to distress, while burnout does not directly relate to turnover intention; distress significantly mediates the pathway between workload and turnover intention but not between burnout and turnover intention. Novelty The model integrates distress as an intervening construct to explain indirect pathways within an industrial workforce context. Implications Findings support managerial policies on workload distribution, psychological support, and preventive strategies to reduce employee withdrawal behavior and strengthen organizational stability. Keywords: Workload, Burnout, Distress, Turnover Intention, Structural Equation Modeling Key Findings Highlights: Work demand shows the strongest direct association with leaving intentions Emotional exhaustion predicts psychological strain among staff Indirect pathway occurs only through the mediating construct